2016
DOI: 10.1021/acs.jpcc.6b04957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anodic Aluminum Oxide Chemistry on Adhesive Bonding of Epoxy

Abstract: The transition to Cr­(VI)-free production is a great challenge in the global aerospace industry that currently still relays on it for the preparation of aluminum for bonding. Proper surface pretreatment is a prerequisite for strong and durable adhesive joint. Despite decades of experience, the nature and contribution of the different adhesion forces between the aluminum and organic adhesive remain under discussion. Herein we studied the adhesion of epoxy resin as a function of the surface chemistry of barrier-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 25 publications
6
41
0
Order By: Relevance
“…5c. The peel strength for such featureless oxides with an epoxy adhesive was previously reported in Abrahami et al 10 Their dry peel strength was in the same order of magnitude as porous oxides with small pores shown here. Once the pores are large enough and the resin penetrates into the pores, sufficient bonding is achieved and no further improvements in peel strength are registered.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…5c. The peel strength for such featureless oxides with an epoxy adhesive was previously reported in Abrahami et al 10 Their dry peel strength was in the same order of magnitude as porous oxides with small pores shown here. Once the pores are large enough and the resin penetrates into the pores, sufficient bonding is achieved and no further improvements in peel strength are registered.…”
Section: Discussionsupporting
confidence: 86%
“…In our earlier study it was reported that interfacial bonding between anodic oxides and epoxy resin proceeds through the hydroxyl groups at the surface of the oxide. 10 The incorporation of phosphate and sulfate anions did not change the bonding mechanism; it only affected the amount of hydroxyl groups available for bonding. It was found that the density of hydroxyl groups at the surface of SAA oxide is larger than for PSA oxides (approximately double, depending on the anodizing conditions).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As opposed to model molecules, adhesive films undergo curing at elevated temperatures and pressures and typically contain extra additives. In a recent work we demonstrated that bonding between barrier-type anodic aluminum oxides and FM 73 epoxy resin is distorted by water 26 . This was postulated to occur due to the reversible nature of hydrogen bonds that were formed between the oxide and epoxy.…”
Section: Introductionmentioning
confidence: 97%